2007
DOI: 10.1001/archinte.167.6.597
|View full text |Cite
|
Sign up to set email alerts
|

The Virologic, Immunologic, and Clinical Effects of Interleukin 2 With Potent Antiretroviral Therapy in Patients With Moderately Advanced Human Immunodeficiency Virus Infection

Abstract: Background: Interleukin 2 (IL-2) administration increases CD4 counts in persons with higher counts. This study investigated persons with moderately advanced human immunodeficiency virus infection receiving highly active antiretroviral therapy (HAART). Methods: Two hundred four patients with CD4 T-cell counts from 50/µL to 350/µL who were treatment naive or had been treated only with reverse transcriptase inhibitors began a specified protease inhibitor HAART regimen. Virologic responders (Յ5000 copies/mL) at 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
1
34
1
Order By: Relevance
“…Based on the Wilhem et al case report, we selected IL-2 at 600 000 IU/day as this was the lowest, well-tolerated dose that produced a significant and undelayed increase in CD4 + cell counts [14].We increased the dose as tolerated to achieve CD4 + counts greater than 300 cells/mm 3 , but unlike other case reports we titrated based on a three doses per week regimen, because of the patient's preference. The weekly 11 million IU (divided into three doses) our patient received exceeded the 7 million IU weekly (1 million daily) that Wilhem et al reported and was fewer than the intermittent doses used in HIV trials [14,[24][25][26][27] ( Table 1).…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Based on the Wilhem et al case report, we selected IL-2 at 600 000 IU/day as this was the lowest, well-tolerated dose that produced a significant and undelayed increase in CD4 + cell counts [14].We increased the dose as tolerated to achieve CD4 + counts greater than 300 cells/mm 3 , but unlike other case reports we titrated based on a three doses per week regimen, because of the patient's preference. The weekly 11 million IU (divided into three doses) our patient received exceeded the 7 million IU weekly (1 million daily) that Wilhem et al reported and was fewer than the intermittent doses used in HIV trials [14,[24][25][26][27] ( Table 1).…”
Section: Discussionmentioning
confidence: 80%
“…+ lymphopenia [21][22][23][24]. However, our patient did not have clinical features consistent with any of these syndromes, a personal or family history of malignancy or a karyotypical analysis consistent with chromosomal instability.…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…Median CD4 + cell count changes at the end of the study (week 84), were +102, +312, and +459 3 10 6 cells/L, respectively, for the HAART only, HAART plus subcutaneous IL-2, and HAART plus intravenous IL-2 groups (P = 0.001). 18 Interestingly, the subcutaneous IL-2 group had the best HRQOL scores overall, but the intravenous group had the best immunologic measures of the 3 treatment groups. HRQOL scores in the intravenous IL-2 group may have been affected by issues of inconvenience and time required for treatment, which were not specifically asked about on our questionnaires.…”
Section: Discussionmentioning
confidence: 91%
“…Several phase II studies have documented IL-2 dose-dependent expansions of CD4 T cells, with increases in naïve and memory subsets due to improved survival and decreased immune activation when administered with HAART [13, 18, 24, 25, 42]. The immune restoration conferred by HAART alone is incomplete, however, despite reductions in CD4 T cell activation, turnover, and lymphopenia [4346].…”
Section: Discussionmentioning
confidence: 99%